2015
DOI: 10.1542/peds.2014-3745
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of a 9-Valent HPV Vaccine

Abstract: OBJECTIVES: Prophylactic vaccination of youngwomen aged 16 to 26 years with the 9-valent (6/11/16/18/31/33/45/52/58) human papillomavirus (HPV) virus-like particle (9vHPV) vaccine prevents infection and disease. We conducted a noninferiority immunogenicity study to bridge the findings in young women to girls and boys aged 9 to 15 years.METHODS: Subjects (N = 3066) received a 3-dose regimen of 9vHPV vaccine administered at day 1, month 2, and month 6. Anti-HPV serologic assays were performed at day 1 and month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 50 publications
8
114
0
3
Order By: Relevance
“…Study objectives: The primary study objectives were: i) to evaluate the safety and tolerability of 9vHPV vaccine when administered to 9-to 15-year-old girls; and ii) to estimate the immune response of subjects to the various vaccine HPV types (6,11,16,18, 31, 33, 45, 52, and 58) at 4 weeks post dose-3, using seroconversion rates. For i), all subjects who received at least 1 vaccine, and had follow-up data were included in the analysis of safety.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study objectives: The primary study objectives were: i) to evaluate the safety and tolerability of 9vHPV vaccine when administered to 9-to 15-year-old girls; and ii) to estimate the immune response of subjects to the various vaccine HPV types (6,11,16,18, 31, 33, 45, 52, and 58) at 4 weeks post dose-3, using seroconversion rates. For i), all subjects who received at least 1 vaccine, and had follow-up data were included in the analysis of safety.…”
Section: Methodsmentioning
confidence: 99%
“…The GMTs were compared for anti-HPV 6, 11, 16, 18, 31, 33, 45, 52, and 58; ii) to describe the persistence of serum antibody titers for the various HPV types 24 months following the third dose of 9vHPV vaccine; and iii) to estimate the immune response of subjects to the HPV types (6,11,16,18, 31, 33, 45, 52, and 58) at 4 weeks post dose-3, using GMTs. The secondary hypothesis was evaluated by comparing GMTs obtained from 9-to 15-year-old girls during month 7, with the GMTs in 16-to 26-year old Japanese young women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of either 2vHPV, 4vHPV, or 9vHPV leads to greater antibody responses in girls and boys 9 through 15 years of age, compared with those in girls and boys 16-through 26 years of age receiving the respective vaccine. 57,58 Pre-and postlicensure studies also have demonstrated safety, immunogenicity, and efficacy for the 2vHPV, 4vHPV vaccines. Each vaccine is highly effective, providing type-specific protection against the included HPV types.…”
Section: Hpv Vaccinesmentioning
confidence: 99%
“…[1][2][3][4][5] In clinical studies, the 9vHPV vaccine prevented persistent infection and disease due to the HPV vaccine types in females 16 to 26 years of age 6 ; efficacy findings were extended to girls and boys 9 to 15 years of age based on noninferior immunogenicity. 7 The 9vHPV vaccine was licensed in the United States in December 2014 under the name GARDASIL9 (Merck & Co., Inc., Kenilworth, NJ). 8 In February 2015, the Advisory Committee on Immunization Practices included GARDASIL9 in its recommendations for routine HPV vaccination of boys and girls at age 11 or 12 years and catchup vaccination in females 13 to 26 years and males 13 to 21 years not vaccinated previously.…”
Section: What This Study Addsmentioning
confidence: 99%